EVALUACIÓN DE LA GESTIÓN ADMINISTRATIVA Y FINANCIERA DE LA COOPERATIVA DE TRANSPORTES URBANOS 24 DE MAYO PERIODO 2016-2017 - CHAVEZ QUINCHE, MARÍA FERNANDA (2019)
Administrative-financial management has now become one of the main strategic tools. The cooperativa de transportes urbanos 24 de mayo of the City of Loja in which it is evident that during the time it has been in the market it needs to have a good control of its financial resources, as well as the application of administrative evaluation mechanisms, where it is not has evaluated the annual budget to determine its efficiency in the management of resources, and the achievement of the objectives set by management; and vertical and horizontal financial analysis and application of financial indicators. In these circumstances the present thesis was carried out based on the General Objective "To carry out the evaluation of the administrative and financial management of the cooperativa de transportes urbanos 24 de mayo periods 2016-2017". This investigation is of descriptive type that consists in applying a vertical analysis, to determine the financial composition of the assets, liabilities and patrimony; horizontal analysis to measure the variation of the accounts from one year to another; and, the application of financial indicators such as liquidity, activity, profitability and indebtedness. It is concluded that the cooperativa de transportes urbanos 24 de mayo in the 2016-2017 period of the City of Loja administratively, although there is a surplus in its results, there is an excess of budgetary execution with respect to what was planned; financially the cooperative demonstrates an increase in passive asset and equity accounts; and, in the income statement it was evidenced that there is an increase in the accounts as it is in inventory since it is characteristic of the company's own activity; while, in the application of financial indicators, the liquidity with the cooperative account is good to cover short-term obligations, but not immediately. Results that were reflected in a financial administrative report aimed at organizational improvement based on cooperativism and their mutual help in order that their managers make the best decisions.